Multiletramentos e tecnologias: formação continuada de professores de Língua Portuguesa na Educação Profissional e Tecnológica - SANTOS, Isabelly Raiane Silva dos (Universidade Federal do Pará, 2024)
This research consists of a theoretical-practical study on the perception that Portuguese language teachers working in Professional and Technological Education (PTE) have when analyzing their own continuing education and its influence on the adequate approach to multiliteracies in the classroom. Thus, based on the support provided by the conceptual bases of PTE, that is, work as an educational principle and integral human training, with regard to the development of practices aimed at continuing teacher training, the multiliteracies emerge as an opportunity to embrace different types of language, so that the individual interprets linguistic situations which deviate from the traditional ones, addressed in the school sphere. In this context, the objective of this research was to understand how the teaching training of Portuguese language teachers working at the Federal Institute of Education, Science and Technology of Pará (IFPA) - Abaetetuba campus is articulated in the context of multiliteracies. Based on Freire (1980, 1985, 1996), Soares (1981, 1999, 2004), Street (1984), Kleiman (1995, 2001, 2007), Gatti (1997), Rojo (2012, 2013), Moura (2014) and Ramos (2014), in this study, an exploratory and qualitative investigation was developed through field research based on the ethnographic approach. The investigation was developed at IFPA - Abaetetuba campus. It was restricted to the context of Integrated High School (IHS). Participants were two Portuguese language teachers working at IHS. Through field visits to generate data, research techniques and instruments were used. Among them, it is possible to mention: direct observation in classes, field diary writing, open questions questionnaire application, descriptive academic memorial writing by the participants and semi-structured interview. In the end, it was highlighted the relevance of continuing training to implement multiliteracies obtained by the Portuguese language teacher working in PTE by understanding, to what extent, technologies contribute to the approach of multiliteracies which prioritize student learning with a focus on the integration between world of work and education.